Uptake of interventions for preventing mother-to-child HIV transmission in 11 operational districts in Cambodia - Sovannarith, Samreth; Sokleng, Sun; Romaing, Tep; Sovanna, Tuon; Welle, Emily; Fujita, Masami; Poudel, Krishna; Barr–DiChiara, Magdalena; Bora, Ngauv; Sopheap, Seng; Sovatha, Mam; Campbell, Penelope; et al. (Western Pacific Surveillance and Response, 2013)
Introduction: To achieve the global goal of eliminating mother-to-child transmission of HIV, retention of HIV-positive women and their babies throughout the cascade of prevention of mother-to-child transmission of HIV (PMTCT) services is necessary. Little evidence has been published on coverage of the cascade in resource-limited settings. Along with PMTCT service expansion in Cambodia, a national routine reporting system was developed. This study examines coverage of six PMTCT interventions to improve our understanding of retention throughout the cascade. Method: We developed indicators to monitor coverage of the six key interventions: (1) maternal antiretroviral treatment or prophylaxis; (2) delivery in a health facility; (3) infant ARV prophylaxis at birth; (4) infant co-trimoxazole prophylaxis at six weeks; (5) first infant DNA-PCR test at six weeks; and (6) second infant DNA-PCR test at 30 weeks. Programme data from April 2008 to December 2011 in 11 operational districts were used to identify those eligible for each intervention. Results: Women eligible for maternal antiretroviral treatment or prophylaxis in the study were aged 18 to 48 with a median age of 30 years. Coverage of the six interventions were: (1) 79.9% (258/323); (2) 92.2% (236/256); (3) 69.9% (179/256); (4) 73.3% (184/251); (5) 85.7% (215/251); and (6) 61.6% (135/219). Among those eligible, 29.7% (65/219) received all six interventions. Discussion: This study revealed critical gaps in PMTCT service delivery under routine conditions in Cambodia. Service optimization by reducing gaps will help eliminate HIV infection among infants and improve maternal survival. Further operational studies are needed to identify determinants of service uptake.